Caesarean Section Without Indwelling Catheter (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Background: Many studies were conducted worldwide on the subject but there is none in Chittagong. To get our experience we had conducted the study. Methods: It was an experimental study. 70 cases were conveniently selected under certain inclusion and exclusion criteria. Cases were managed by the obstetricians unrelated to the study. All cases were meticulously observed by the investigators and findings were instantly recorded. All data were manually managed. A discussion was made and conclusion was drawn. Results: Total 70 cases were studied. 35 primae and 35 multipara. Mean age was 27 years +2.3 . All were literate and 86% were housewives. Cases were without medical, surgical complications and were uneventfully managed. First voiding time was 4.28 hours +0.45. 07% cases were evacuated with plain catheter after 7 hours for pain and bladder distention. Average hospital stay 2.3 days. There was no occurrence of urinary tract infection. Conclusion: Indwelling catheter should not be used unless it is strongly indicated. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22878 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 34-35